AI-DRIVEN AUTOMATION OF PUBLIC ASSISTANCE PROGRAM ELIGIBILITY: A TECHNICAL ANALYSIS - Sri Rama Satya Prasanth Vuppuluri, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This technical article explores the application of Artificial Intelligence in automating the eligibility determination process for major public assistance programs, including SNAP (Supplemental Nutrition Assistance Program), TANF (Temporary Assistance for Needy Families), and MA (Medical Assistance). The article examines the current challenges in manual processing systems, presents a comprehensive framework for AI implementation, and analyzes the technical architecture required for successful deployment. It covers data pipeline components, machine learning frameworks, implementation methodologies, bias mitigation strategies, security controls, performance metrics, and future scalability considerations. Through case studies and empirical data, the analysis demonstrates how AI-driven systems can significantly improve processing efficiency, reduce errors, and enhance the overall effectiveness of public assistance programs while maintaining fairness and compliance with regulatory requirements.